Maximum Self-Consumption Planning Framework Considering Energy Management System for Optimal Photovoltaic-Battery System in Distribution Network (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Power production from photovoltaic (PV) has advanced as Renewable Energy Resources (RES) power technology and is now a worthwhile alternative to conventional power generating. To effectively stabilize the process of connecting to the grid and increase power controllability owing to changing PV power production, energy storage systems (ESS), with their flexible charging and discharging capabilities, are most often used to cooperate with RES power generation. However, ESS's rapid rate of charging and discharging might cause it to age more quickly than it should and reduce its lifespan. Therefore, this study proposed an effective planning framework of optimal penetration of PV-ESS system associated with effective energy management systems (EMS). The proposed framework, the optimal PV size, PV location and maximum State of Charge (SOCmax) are determined. The fixed minimum State of Charge (SOCmin) based on load conditions is applied to minimize the degradation while maximizing PV self-consumption. The result shows that when applying different SOCmin during at off-peak and peak time load demand, the degradation cost is reduced to 19.40%.
Keywords: Energy; Energy Management System; Renewable Energy; Optimization; Battery degradation; State of Charge